KARAKTERISTIK FOURIER TRANSFORM INFRA RED DAN KEKUATAN BENTUR KOMPOSIT POLIESTER TAK JENUH BERPENGISI ABU SEKAM PADI PUTIH - Caroline Oktaviana Hutagalung; Maulida (Jurnal Teknik Kimia USU, 2014)
This study was aimed to investigate the effect of white rice husk ash as filler in Fourier Transform Infra Red (FTIR) caractheristic and impact strength of polyester composites. The composites were made with open mixing method by mixing unsaturated polyester with white rice husk ash with the composition of each fillers of 5,10, 15, and 20 % (w/w) then added with 1% methyl ethyl ketone peroxide as catalizer. The parameters which was carried on the prepared samples was characteristic of FTIR and impact strength. It was found that impact strength increased at each of composition of fillers white rice husk ash (WRHA). The optimum value of unsaturated polyester composite filled WRHA are 7031 J/m2 and 8297,333 J/m2 for particle size maximum 100 and 250 mesh.